Market power and competitive policy on the market of tourism services insurance. - Suslikov, А.; Sirenko, O.; Karman, S.; Pochernina, Nataliia; Почерніна, Наталя Вікторівна; Zakharchenko, O.; Vasylchenko, O.; Васильченко, Олена Олегівна (My University, 2021)
EN : Man’s desire for self-development through knowledge of the world, the realization of his right to rest are manifested in tourism. The development of tourism is also facilitated by globalization and international integration, visa liberalization with individual countries, as well as international economic and political unions. An effective tool for minimizing risks in tourism is insurance. Despite the long period of forming, the market of travel insurance in Ukraine still does not meet international standards, occupies a small place in the system of insurance services. The purpose of this study is the analysis of concentration on the market of tourist services insurance in Ukraine. The state and tendencies of concentration in the market of travel insurance in Ukraine are analyzed. Lorentz’ concentration curves in the market of medical expenses insurance are constructed. It has been shown that insurance in the market of medical expenses is essential for the development of tourism in Ukraine, especially outbound. In this system of provided insurance services the quality of tourist services should come first, which can be achieved only under conditions of perfect competition, state regulation and implementation of international insurance standards. It has been established that during 2014—2020 there were processes of increasing the market power of insurance companies, an oligopoly is formed with four or six main players. It has been shown that the leaders of insurance in the market of tourist services are large insurance companies with foreign capital, operating at the international level. Their gradual concentration in recent years indicates the improvement of the institutional framework of tourist insurance, and the increase in insurance premiums and insurance payments indicates the restoration of confidence of Ukrainians in insurers.////////// UA : Прагнення людини до саморозвитку через пізнання світу, реалізація його права на відпочинок знаходять свій прояв у туризмі. Розвиткові туристичної діяльності також сприяють глобалізація й міжнародна інтеграція, лібералізація візових режимів як з окремими країнами, так і міжнародними економічними й політичними союзами. Дієвим інструментом мінімізації ризиків у туризмі є страхування. Незважаючи на тривалий період становлення, ринок страхування туристичних послуг в Україні й донині не відповідає міжнародним стандартам, займає незначне місце в системі страхових послуг. Метою дослідження є аналіз концентрації на ринку страхування туристичних послуг в Україні. Проаналізовано стан і тенденції концентрації на ринку страхування туристичних послуг в Україні. Побудовано криві Лоренца концентрації на ринку страхування медичних витрат. Показано, що страхування на ринку медичних витрат має істотне значення для розвитку туризму в Україні, особливо виїзного. У цій системі надаваних страхових послуг на перше місце має виходити якість обслуговування туристів, чого можна досягти тільки за умов досконалої конкуренції, державного регулювання й впровадження міжнародних стандартів страхової діяльності. Установлено, що протягом 2014—2020 рр. відбуваються процеси нарощення ринкової влади страхових організацій, формується олігополія з чотирма — шістьма основними гравцями. Показано, що лідерами страхування на ринку туристичних послуг є великі страхові компанії з іноземним капіталом, що здійснюють свою діяльність на міжнародному рівні. Їхня поступова концентрація протягом останніх років вказує на удосконалення інституціональних засад страхування туристів, а збільшенням обсягів страхових премій і страхових виплат — свідчить про відновлення довіри українців до страховиків.
Ринкова влада і конкурентна політика на ринку страхування туристичних послуг.
Keywords: market power; insurance; concentration; competitive policy; tourism; risks; market; ринкова влада; концентрація; конкурентна політика; страхування; туризм; ринок; ризики